2016
DOI: 10.1016/j.jaci.2015.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of inflammatory innate lymphoid cells in patients with common variable immune deficiency

Abstract: Background Common variable immunodeficiency (CVID) is an antibody deficiency treated with immunoglobulin; however, patients can have noninfectious inflammatory conditions that lead to heightened morbidity and mortality. Objectives Modular analyses of RNA transcripts in whole blood previously identified an upregulation of many interferon-responsive genes. In this study we sought the cell populations leading to this signature. Methods Lymphoid cells were measured in peripheral blood of 55 patients with CVID … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 46 publications
(85 reference statements)
8
53
1
3
Order By: Relevance
“…It is deregulated in the development of psoriasis, Crohn’s disease, and other forms of autoimmunity such as the multiple sclerosis model experimental autoimmune encephalomyelitis (EAE). Consistent with this, investigators have reported ILC3 expansion in: skin and blood of patients with psoriasis (9799); blood, gut, synovial fluid, and bone marrow of patients with ankylosing spondylitis (100); and blood, lung, and gut of patients with common variable immunodeficiency (CVID) (101). Interestingly, several labs have reported that ILC3 are reduced rather than increased in Crohn’s disease relative to ILC1 (17, 18, 57, 58), and that remaining ILC3 are phenotypically altered and express less MHC-II (102).…”
Section: Module 3: Extracellular Bacteria and Fungimentioning
confidence: 61%
“…It is deregulated in the development of psoriasis, Crohn’s disease, and other forms of autoimmunity such as the multiple sclerosis model experimental autoimmune encephalomyelitis (EAE). Consistent with this, investigators have reported ILC3 expansion in: skin and blood of patients with psoriasis (9799); blood, gut, synovial fluid, and bone marrow of patients with ankylosing spondylitis (100); and blood, lung, and gut of patients with common variable immunodeficiency (CVID) (101). Interestingly, several labs have reported that ILC3 are reduced rather than increased in Crohn’s disease relative to ILC1 (17, 18, 57, 58), and that remaining ILC3 are phenotypically altered and express less MHC-II (102).…”
Section: Module 3: Extracellular Bacteria and Fungimentioning
confidence: 61%
“…Similarly, Innate lymphoid cells (ILC) have also been identified to play a crucial role in IBD pathogenesis [26]. The number of inflammatory ILC have remarkably been found increased in blood, respiratory and gastrointestinal mucosa of CVID patients with inflammatory conditions compared to patients without CVID inflammatory disorders [27] although, to date ILC have not been studied in detail in the GI mucosa of CVID patients with intestinal manifestations.…”
Section: Non-infectious Complications Of Cvid (Table 1)mentioning
confidence: 99%
“…IgG replacement therapy reduces immune activation in CVID patients (13), but invariant NK T cells and regulatory T cells remain low in CVID patients on treatment (14)(15)(16). Chronic upregulation of the IFN pathway, due to expansion of proinflammatory group 3 innate lymphoid cells, has been reported in a subset of CVID patients with inflammatory complications (17,18).…”
Section: Introductionmentioning
confidence: 99%